Forecasting ECB policy rates with different monetary policy rules - Ansgar Belke; Jens Klose (Research On Money in the Economy (ROME), 2019)
This article compares two types of monetary policy rules - the Taylor-Rule and the Orphanides-Rule - with respect to their forecasting properties for the policy rates of the European Central Bank. In this respect the basic rules, results from estimated models and augmented rules are compared. Using quarterly real-time data from 1999 to the beginning of 2019, we find that an estimated Orphanides-Rule performs best in nowcasts, while it is outperformed by an augmented Taylor-Rule when it comes to forecasts. However, also a no-change rule delivers good results for forecasts, which is hard to beat for most policy rules.
Keywords: E43; E52; E58; C53; 330; Taylor-Rule; Orphanides-Rule; Monetary Policy Rates; Forecasting; European Central Bank